Development of banana geotextile-reinforced geopolymer mortar as confinement material on axially loaded concrete - Pilien, Vincent Pardo (Animo Repository, 2023)
Confinement of concrete using different materials and procedures is an effective method of strengthening weak and deteriorated concrete structural members especially those under axial compression. Recently, textile reinforced mortar (TRM) has become popular as a confinement material. TRM consists of high strength fibers with open mesh grid configurations bonded by inorganic matrix like lime or cement-based mortars. TRM usually contains environmentally harmful materials that can affect the ecosystem. To lessen the environmental impact of traditional materials, a more environmentally friendly confinement using natural fibers and cement-free mortars has become a subject of recent studies. To address the challenge of developing a confinement material for axial compression members that is effective and environmentally friendly, a novel banana geotextile-reinforced geopolymer mortar (BGT-RGM) was developed in this study. BGT-RGM is composed of banana geotextile (BGT) and engineered geopolymer composite (EGC) reinforced with 10mm short banana fibers (BF). The EGC is a fly ash (FA) based geopolymer reinforced with 10mm short BFs and the banana geotextiles are fabricated from twined 2mm diameter BF cords. The experimental study on the development of BGT-RGM involves various phases. The first phase, which is Banana Fiber Extraction and Treatment aims to optimize a treatment solution that will enhance the physical and mechanical properties of banana fiber suitable as reinforcement. After treatment, mechanical, physical, chemical, and microstructural analysis of the treated and untreated banana fibers were conducted after the elimination of fibers through manual testing of fibers to determine the top performing banana fibers that will be used for reinforcing the EGC. After nine different treatment solutions with 2, 4 and 6 % of sodium hydroxide (NaOH) within 2, 4 and 6 hours, phase 1 resulted to selecting a length of short fibers of 10mm to be used as reinforcement of the EGC to reduce the brittleness of geopolymer and prevent the occurrence of macro cracks. The next phase involves the optimization of plain geopolymer mortar (PGM) and EGC mortar was carried out to find the optimum mixtures to be reinforced with top performing fibers during the manual and machine testing of fibers. The PGM and EGC mortar were prepared by using FA and silica fume (SF) as binders and sand as filler, then it was activated by an alkali solution composed of NaOH and WG. With the inclusion of silica fume, which is commonly used pozzolanic material, in the geopolymer, the durability of the composite was enhanced. There were 13 different experimental runs for EGC mortar while 8 experimental runs were conducted for the PGM. The optimum design mix for EGC mortar (DM1-12) which has 1% of BF, 0.2 water to solids ratio, 0.54 NaOH to WG ratio, 1.5 (FA+SF) to sand ratio, and 5 % SF. while for optimum design PGM (DM1-04) which has 0% of BF, 0.2 water to solids ratio, 0.6 NaOH to WG ratio, 1.5 (FA+SF) to sand ratio, 5 % SF. The optimum EGC and PGM on the optimization were adopted to investigate the effect of top performing TBFs and UBF with respect to split tensile and compressive strength tests. The design mix (DM1-12) with the highest compressive and split tensile strength is selected on the development of the confinement model. The final phase of the study is the development of the BGT-RGM. In this phase the optimum EGC design mixture (EGC-3) was used as mortar on 12 BGT-RGM mixtures as confinement of the M15 concrete cylinder. Different varying parameters were considered on the BGT-RGMs including the 12mm and 20mm thickness of EGC mortars, 15mm, 20mm and 25mm banana geotextile grid spacing and 6 BGT-RGM were coated with polymer while the remaining 6 BGT-RGMs are uncoated with polymer. The EGC-3 reinforced with TBF2 treated with 4% of NaOH within 4 hours governed the compressive and split tensile test giving 23.98 and 2.06 MPa respectively. These 12 BGT-RGM designs were compared to unconfined 100x200mm M15 concrete cylinder in terms of compressive strength and local crack formation mode of failure using digital image correlation (DIC) software. A confinement and regression model were also presented to estimate the theoretical ultimate compressive strength and effectiveness of confinement. The governing BGT-RGM 4 and 5 mode of failures initiated through the local formation of cracks near mid-bottom and mid-height that caused rupture of the mortar while the CS damage initiated through the formation of cracks near mid-bottom and mid-height of the concrete which continued along the length of the cylinder and successfully mapped by the DIC software. Based on Mander’s confinement model, f ’cc = f ’co + k • f l, the values of the confinement effectiveness and theoretical compressive strength were obtained and used on the regression model with linear equation y = 0.8975x + 1.9051 and coefficient of correlation, = 0.8975 which signifies good values of the actual f’cc wherein 89.75% of the variation is explained by the model. With these substantial findings and new discoveries, the designed and novel BGT-RGM 4 as confinement material reinforced with banana geotextiles from woven 2mm diameter of twined BF cords and impregnated by a 20mm thick EGC mortar reinforced with 10mm short banana fibers was successfully developed. With the significant modification of banana fibers through alkali treatment utilizing 4% of NaOH within 4 hours reinforcing the optimum EGC mortars provided a 33.3% increase in compressive strength when the axially loaded M15 concrete is confined. Thus, the use of BGT-RGM confinement as concrete strengthening materials is a more environmentally friendly technology and effective that can provide significant increase in axial strength of concrete.